Responsabilidad social empresarial: gobernanza corporativa, empresa y ONG = Corporate social responsability : corporate governance, business and NGO - Sánchez Fernández, Maria Dolores (Oñati Socio-Legal Series, 2012)
To carry out various activities related to corporate social responsibility corporations identify the different stakeholders of the organization, in which NGOs are found. The study carried out was to analyze what role charity organizations play and the role they should pursue in corporate governance as stakeholders of the organization. The organizations claim that they intervene as auditors of the codes of conduct developed by companies. There are forces that inhibit collaboration between companies and NGOs, but there are also strategies that coexist which the latter can adopt in order to achieve collaboration between the two. It becomes manifest that the third sector is not a synonym of NGOs, but that these organizations are a component of it. The benefit of public private partnerships for society and the power that companies obtain, especially multinationals, the evasion of responsibilities with regard to the preservation of human rights is raised in the debate. This work debates the role which NGOs acquire with reference to codes of conduct adopted by companies. Finally, given its relevance, the case of the Red Cross is studied.